New horizons in Medical Law amidst a global pandemic - Jahn Kassim, Puteri Nemie (2021)
The outbreak of Covid-19 has affected countries all over the world. In handling the outbreak, governments had to implement stringent public health measures with far-reaching consequences on personal liberties and human rights. Imposing stringent quarantine mandates emergency lockdown policies and mandatory Covid-19 testing on millions of people have triggered a plethora of legal issues. Medical law, in particular, have subsumed into new horizons requiring deliberation and understanding as to the changes in the rights of patients, liabilities of members of the medical profession and responsibilities of healthcare providers. The shortage of medical staff in handling the surge of patients admitted to the hospital has caused healthcare providers to implement desperate measures in requiring their medical staff to assist beyond their area of expertise. In such circumstances, arising negligence issues may trigger legal complications as to the scope of legal responsibilities of the relevant medical staff as well as the healthcare providers. Subjecting patients to mandatory Covid-19 testing have inadvertently triggered legal issues in the area of consent as legally valid consent is considered a requisite to waive any claims in trespass to a person’s body. Revealing personal information in newspapers and social media on patients suspected of having Covid-19 has also compromised their right of privacy and confidentiality causing social stigmatization and discrimination. Thus, the aim of this presentation is to look into three main areas in the development of medical law amidst the outbreak of Covid-19, namely; (i) issues on negligence in situations of crisis in defining the rights of patients and potential liabilities of the medical profession as well as the healthcare providers (ii) issues on the scope of medical consent in situations of emergencies; and (iii) issues on medical confidentiality arising from the discussion of patients’ identities in social media. Despite the myriad of problems caused by the Covid-19 pandemic crisis which necessitated changes in several legal areas, the development of Medical Law must still flourish in accordance with the principles of human rights, rule of law and good governance.